Pelatihan Storytelling pada Pengelola Wisata di Desa Budo - Benny Irwan Towoliu; Mikhael C.S. Mangolo; Alma K. Pongtuluran; Jeanlly A. Solang; Fonny Sangari (Jurnal Ragam Pengabdian, 2025)
The narrative of each product in a destination needs to be conveyed by telling the uniqueness of each product to arouse curiosity among visitors or tourists. Storytelling in the context of tourism is a method of conveying a story through words, images, or other media, with the aim of conveying information, entertaining, or influencing guests. Budo is a tourist village that has many potential attractions with backgrounds that are said to be myths or actual events, but the managers have never realized that the stories behind these attractions can be memorable for tourists visiting the location. Storytelling training equips tourism managers with various skills and abilities, such as speaking skills, thinking skills, and creativity in managing the existing tourism potential to the maximum. Training methods: opening or orientation, core storytelling activities, and closing or evaluation. The primary focus is on creating engaging stories with a strong core and a structured narrative flow. Through this training, managers can develop storylines for each potential attraction and communicate them effectively.